2019
DOI: 10.1108/ijqrm-09-2017-0197
|View full text |Cite
|
Sign up to set email alerts
|

Reliability engineering application to pipeline design

Abstract: Purpose The purpose of this paper is to investigate the application of reliability engineering to oil and gas (O&G) pipeline systems with the aim of identifying means through which reliability engineering can be used to improve pipeline integrity, specifically with regard to man-made incidents (e.g. material/weld/equipment failure, corrosion, incorrect operation and excavation damages). Design/methodology/approach A literature review was carried out on the application of reliability tools to O&G pipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Oil and gas pipelines are the safest and most efficient and effective mode of fluid transportation when compared to rail or road transport; however, the consequences of failure can be extreme. Omoya et al (2019) found that pipeline incidents on the US cost an average of $414 Million each year, not accounting for injuries or fatalities. More than 80% of pipeline incidents are the result of human actions with causes including: material, weld, and equipment failures; corrosion; incorrect operation; and excavation damages.…”
Section: Oil and Gas Industrymentioning
confidence: 99%
See 3 more Smart Citations
“…Oil and gas pipelines are the safest and most efficient and effective mode of fluid transportation when compared to rail or road transport; however, the consequences of failure can be extreme. Omoya et al (2019) found that pipeline incidents on the US cost an average of $414 Million each year, not accounting for injuries or fatalities. More than 80% of pipeline incidents are the result of human actions with causes including: material, weld, and equipment failures; corrosion; incorrect operation; and excavation damages.…”
Section: Oil and Gas Industrymentioning
confidence: 99%
“…The application of reliability tools can reduce the number of pipeline incidents. Survey and literature data indicate a reliability-centered approach can be successfully applied to improve oil and gas pipeline reliability (Omoya et al, 2019). An RCM approach includes: (1) reliability centered designwhere an engineer can determine the root causes of failure and quantitatively determine which failure events are most likely to occur and thus focus on them during design with the aim of preventing them; (2) condition monitoringwhere monitoring of identified critical components and data gathering occurs; and (3) reliability centered maintenance which focuses on reducing the number of maintenance tasks that and ensures the reliability of the system.…”
Section: Oil and Gas Industrymentioning
confidence: 99%
See 2 more Smart Citations
“…The application of reliability engineering to oil and gas pipeline systems was investigated by Omoya et al [30] to identify which reliability engineering can be used to improve the integrity of pipelines.Patil [31] identified critical human and organizational factors and their effects on the reliability and maintainability of computerized numerical control.Tsarouhas [32] investigated the implementation of six sigma (SS) strategy with RAM analysis in a bag sector under actual operating circumstances. Moreover, the time-dependent reliability of the harmonic drive was analyzed by Zhang et al [33].Jakkula et al [34] studied the reliability analysis of a load haul dumper in order to apply adequate maintenance management.…”
Section: Introductionmentioning
confidence: 99%